Exploring Academic Note Taking Practices of Multilingual University Students: Perceptions and Practices - Findlay, Alice M, Ms. (AUC Knowledge Fountain, 2026)
Note taking is a fundamental academic skill that records information and supports the identification, selection and organization of information for understanding and knowledge creation, yet it is often overlooked in higher education. Research has explored the role of note taking in supporting learning and examined similarities and differences between L1 and L2 note taking. However, few studies have focused on multilingual students in English Medium Instruction (EMI) contexts despite the additional cognitive challenges of managing information across languages and navigating Western-centric academic conventions. This study investigates how multilingual students at an Egyptian EMI university take notes in their learning contexts. Using a mixed-methods research design, quantitative and qualitative data were collected from 18 multilingual students. The study explores how students take notes and their attitudes and perceptions of note taking in relation to learning. Findings indicate that note taking amongst multilingual students is dynamic and multifaceted. Participants flexible adapt note taking strategies, tools and methods, integrating sources from textbooks to digital tools, including artificial intelligence (AI). Participants demonstrate metacognitive awareness by adjusting their approaches to task demands and managing cognitive load, while also expressing a clear desire for explicit instruction in note taking. Participants view note taking as an important tool for effective learning and academic success. These findings align with previous research that conceptualizes note taking not as a mechanical recording activity but as a cognitive and strategic process that underpins learning. This study suggests that EMI institutions should integrate explicit note taking instruction within disciplinary courses, recognizing multilingual students as capable learnings and leveraging their linguistic and academic resources to support comprehension, meaning-making and academic progress.